Experimental and numerical assessment of the effect of speed and loading conditions on the nominal wake of a containership - Carlo Giorgio Grlj; Nastia Degiuli; Ivana Martić (Brodogradnja)
An important aspect of the design of the propeller is the determination of the nominal wake. In this study, the nominal wake of a Post Panamax containership is determined numerically and experimentally at different speeds and loading conditions. The numerical simulations are based on the Reynolds averaged Navier Stokes equations, which are discretized using the finite volume method and the system of equations is closed using the Shear stress transport turbulence model. The nominal wake is determined with numerical simulations that model the effects of the free surface and without the free surface included, i.e., double body simulations. The verification study is conducted to assess the numerical uncertainty for the grid size and time step. The validation study includes a comparison of the contours of the dimensionless axial velocity component, the radial distributions of the circumferentially averaged dimensionless axial velocity components, and the integral values of the nominal wake. The effect of speed is more noticeable for the results obtained with EFD in comparison to the numerically obtained results, which is especially pronounced for the integral value of the nominal wake. The integral value of the nominal wake increases with the increase in the trim angle.